IDENTIFICATION OF PRODUCTIVITY VALUES USING THE METHOD PRODUCTIVITY DELAY MODEL ON WALLER BEAM WORK - Melvin Yeremia; Ryobi Irfanto (LPPM Universitas Negeri Jakarta, 2025)
Productivity can be interpreted as a comparison between physical output and real output with the actual input. This research aims to identify labor productivity on waller beam installation work in construction projects using the Method Productivity Delay Model (MPDM). The research method is carried out by conducting direct observations in the field and collecting productivity data using MPDM which is applied through delay analysis in the production cycle, techniques for evaluating work team balance and ensuring optimal labor allocation. The results showed that several factors, such as the environment contributing to the waller beam installation contributed 0.04, equipment factor contributed 0.21, labor factor contributed 0.36, material factor contributed 0.15, and management by 0.02 contributed to the delay and lower productivity. Ideal productivity was obtained at 1.737 units/s, overall productivity at 1.486 units/s, and % Achieved Productivity based on Ideal Productivity at 85.54%. In addition, the findings also emphasize the importance of proactive planning and real-time monitoring to reduce productivity losses and improve construction project performance.